A PRELIMINARY STUDY OF DIFFERENTIALLY EXPRESSED GENES IN MALAYSIAN COLORECTAL CARCINOMA CASES - Sim E U H; Bong I P N; Balraj P; Tan S K; Jamal R; Sagap I; Nadeson S; Rose I M; Lim P K M (Tropical Life Sciences Research, 2006)
Presently, the complete genetic mechanisms for the progression of adenoma to carcinoma for colorectal carcinoma (CRC) remain largely unclear. In order to obtain genetic information of this cancer pathway, we searched for differentially expressed genes in tumours of CRC. Gene expression profiles from CRC cases were assessed via the DNA microarray system. We report up-regulation and down-regulation of 819 and 98 genes respectively, in the tumours relative to their normal controls. The differential expression patterns of 121 genes were persistent in all tumours. Thirty three of these are ribosomal proteins (RPs) genes. Comparison of the 121 genes with a public domain gene expression database, the Cancer Gene Expression Database (CGEP), revealed 47 genes to be consistently differentially expressed in colorectal tumours. Among these, 22 are RP genes. Among all RP genes identified in this study the over-expression pattern for six of them is consistent with literature. The up-regulation of RP L32 in CRC tumours was demonstrated for the first time in this study and it was also verified via reverse transcription-polymerase chain reaction (RT-PCR) analysis. Non-RP genes worth noting are the tumour susceptibility gene (TSG101) and the 20-kDa myosin light chain (MLC-2). Albeit small sample size (n = 2 for microarray analysis), our preliminary studies revealed many genes that are brought into the context of CRC tumourigenesis for the first time, thus providing new clues to the genetic events during colorectal carcinogenesis.Setakat ini, mekanisme genetik yang lengkap tentang kemajuan adenoma kepada karsinoma dalam karsinoma usus besar masih belum diketahui. Demi memperoleh maklumat genetik tentang lintasan karsinogenesis ini, kami menggunakan kaedah pencarian gen yang diekspres secara berbeza dalam tumor karsinoma usus besar. Profil pengekspresan gen daripada kes karsinoma usus besar dikaji menggunakan sistem DNA Microarray. Kami melaporkan pengawalaturan tinggi dan rendah untuk 819 dan 98 gen masing-masing dalam tumor relatif kepada kawalan normal berkenaan. Corak pengekspresan berbeza dalam 121 gen adalah kekal dalam semua tumor yang dikaji. Tiga puluh tiga daripada gen-gen ini adalah gen protein ribosom (RP). Perbandingan data dengan pangkalan data pengekspresan gen domain awam (Cancer Gene Expression Database, CGED) menunjukkan 47 gen pengekspresan berbeza adalah konsisten. Dua puluh dua daripada gen-gen ini adalah gen RP. Antara semua gen RP yang dikenal pasti dalam kajian ini, corak pengekspresan untuk enam gen adalah selaras dengan sorotan kajian. Pengekspresan tinggi gen RP L32 dilaporkan buat pertama kali dalam kajian ini dan telah disahkan melalui penganalisaan RT-PCR. Gen-gen yang tidak berkaitan dengan RP tetapi penting untuk dipertimbang adalah gen tumour susceptibility (TSG101) dan 20- kDa myosin light chain (MLC-2). Walaupun penganalisaan microarray kami berdasarkan saiz sampel kecil (n = 2), kajian awal ini mengenal pasti banyak gen yang dikaitkan dengan konteks pembentukan dan kemajuan karsinoma usus besar buat pertama kali. Maka, penemuan kami membekalkan maklumat baru untuk kejadian genetik dalam proses karsinoma usus besar.